Toward a New Collective Biography: The University of British Columbia Professoriate, 1915–1945 - Bruneau, William (Canadian Journal of Education/Revue canadienne de l'éducation, 1994)
Collective biography traditionally relies on quantitative evidence to explain social and economic characteristics of a group of persons. A recent and continuing study of the professoriate at the University of British Columbia between 1915 and 1945 shows that this historical method could and should take into account the intellectual and emotional circumstances of its subjects, rather than rely exclusively on socio-economic data. The UBC study uses several techniques that connect quantitative and circumstantial data in a single, integrated historical argument. La biographie collective repose généralement sur des données quantitatives pour expliquer les caractéristiques sociales et économiques d’un groupe de personnes. Une étude récente, et toujours en cours, du corps professoral à l’University of British Columbia entre 1915 et 1945 indique que cette méthode historique pourrait et devrait prendre en compte le contexte intellectuel et affectif dans lequel se trouvent les sujets, plutôt que de s’en tenir exclusivement aux données socio-économiques. L’étude de l’UBC fait appel à plusieurs techniques qui établissent des liens entre les données quantitatives et contextuelles dans une interprétation historique intégrée.